Glutamic acid decarboxylase isoform distribution in transgenic mouse septum: an anti-GFP immunofluorescence study - ŞEHİRLİ, ÜMİT SÜLEYMAN; VERİMLİ, URAL (SPRINGER, 2016)
The septum is a basal forebrain region located between the lateral ventricles in rodents. It consists of lateral and medial divisions. Medial septal projections regulate hippocampal theta rhythm whereas lateral septal projections are involved in processes such as affective functions, memory formation, and behavioral responses. Gamma-aminobutyric acidergic neurons of the septal region possess the 65 and 67 isoforms of the enzyme glutamic acid decarboxylase. Although data on the glutamic acid decarboxylase isoform distribution in the septal region generally appears to indicate glutamic acid decarboxylase 67 dominance, different studies have given inconsistent results in this regard. The aim of this study was therefore to obtain information on the distributions of both of these glutamic acid decarboxylase isoforms in the septal region in transgenic mice. Two animal groups of glutamic acid decarboxylase-green fluorescent protein knock-in transgenic mice were utilized in the experiment. Brain sections from the region were taken for anti-green fluorescent protein immunohistochemistry in order to obtain estimated quantitative data on the number of gamma-aminobutyric acidergic neurons. Following the immunohistochemical procedures, the mean numbers of labeled cells in the lateral and medial septal nuclei were obtained for the two isoform groups. Statistical analysis yielded significant results which indicated that the 65 isoform of glutamic acid decarboxylase predominates in both lateral and medial septal nuclei (unpaired two-tailed t-test p < 0.0001 for LS, p < 0.01 for MS). This study is the first to reveal the dominance of glutamic acid decarboxylase isoform 65 in the septal region in glutamic acid decarboxylase-green fluorescent protein transgenic mice.
Keywords: Gamma-aminobutyric acid; Glutamic acid decarboxylase; Green fluorescent protein; Septal area; Septal nucleus; GREEN FLUORESCENT PROTEIN; GAMMA-AMINOBUTYRIC-ACID; MESSENGER-RNAS; RAT-BRAIN; COMPARATIVE LOCALIZATION; ALZHEIMERS-DISEASE; GABAERGIC NEURONS; LATERAL SEPTUM; 2 FORMS; REGION